Bilirubin regulates cell death type by alleviating macrophage mitochondrial dysfunction caused by cigarette smoke extract - Jingjing Wei; Yuan Tian; Jinshu Wei; Meiqi Guan; Xiaoya Yu; Jianing Xie; Guoquan Fan (Redox Report)
Objectives To explore the effects and mechanisms of bilirubin on mitochondrial function and type of macrophage cell death after exposure to cigarette smoke extract (CSE).Methods RAW264.7 macrophages were treated with different concentrations of CSE and bilirubin solutions and divided into four groups: control, CSE, bilirubin, and bilirubin + CSE groups. The necrotic and apoptotic states of the macrophages were determined using an Annexin V-fluorescein 5-isothiocyanate/propidium iodide (FITC/PI) staining kit. Cytoplasmic NOD-like receptor family, pyrin domain containing 3 (NLRP3) expression in macrophages was detected by immunofluorescence and the levels of IL-1β and IL-18 in the supernatants of culture medium were detected by enzyme linked immunosorbent assay (ELISA) test. A JC-1 mitochondrial membrane potential detection kit was used to assess mitochondrial membrane damage and the adenosine triphosphate (ATP) assay kit was used to determine intracellular ATP levels. After the macrophages were stained with reactive oxygen species (ROS) specific dye, 2',7'-Dichlorodihydrofluorescein diacetate (DCFH-DA), the fluorescence intensity and proportion of ROS-positive macrophages were measured using flow cytometry.Results We observed that compared with those of 0 μM (control group), concentrations of 5, 10, or 20 μΜ bilirubin significantly decreased cell viability, which was increased by bilirubin exposure below 1 μM. The effect of CSE on macrophage viability was concentration- and time-dependent. Bilirubin of 0.2 μM could alleviate the inhibition of macrophage viability caused by 5% CSE. In addition, bilirubin intervention could reduce the occurrence of necrosis and pyroptosis to a certain extent.Conclusions CSE could cause mitochondrial dysfunction in macrophages, as demonstrated by a decrease in mitochondrial membrane potential and intracellular ATP levels and an increase in ROS production, while bilirubin could relieve mitochondrial dysfunction caused by CSE.